Theoretical aspects of the creation of highly efficient refractories on the basis of SHS technology - Kazhikenova, S. Sh.; Nurkenov, O. A.; Satbaev, B. N. (Springer US, 2011)
The theoretical principles behind the self-propagating high-temperature synthesis of refractory materials are established. The physico-chemical characteristics of these materials are studied and the technology for their production is optimized. The thermochemical and kinetic parameters of the solid-phase combustion of systems based on fireclay, chromite, magnesium sulfate, and aluminum are examined; the phase composition and thermodynamic and physico-mechanical characteristics of the combustion products are determined and formulations are developed for refractory concretes and gunites.
Keywords: self-propagating high-temperature synthesis; SHS-technology; refractory materials; chromium-oxide materials; chromium-corundum refractories; aluminothermy; heat resistance; mechanical strength at high temperatures